Questions on the taxonomic status of species of Protoholozoa Kott 1969 (Ascidiacea, Aplousobranchia, Holozoidae) with a description of a new genus - Monniot, Françoise; Tatián, Marcos (Zootaxa, 2020)
Among numerous ascidians, two colonies of the deep species Protoholozoa pedunculata Kott, 1969 were collected in 2017 by the French Poker 4 survey, Indian Ocean. The larvae of this species are described here for the first time. The present material shows the disposition of adhesive papillae in a line and incubation in the atrial cavity. That is different from what was first reported and from what is known in other species of the genus, which show triradiate adhesive papillae and incubation in a brood pouch. This new data leads us to discuss the taxonomic status of different species, leaving Protoholozoa Kott, 1969 for the previous ones and creating Scotiazoa gen. nov. for species with triradiate larval papillae and brood pouch.